2020
DOI: 10.1038/s41598-019-56962-2
|View full text |Cite
|
Sign up to set email alerts
|

Group task-related component analysis (gTRCA): a multivariate method for inter-trial reproducibility and inter-subject similarity maximization for EEG data analysis

Abstract: Group task-related component analysis (gtRcA): a multivariate method for inter-trial reproducibility and inter-subject similarity maximization for eeG data analysis Hirokazu tanaka eeG is known to contain considerable inter-trial and inter-subject variability, which poses a challenge in any group-level EEG analyses. A true experimental effect must be reproducible even with variabilities in trials, sessions, and subjects. extracting components that are reproducible across trials and subjects benefits both under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…The results showed that this method significantly improves the information transfer rates and classification accuracy. Based on this research, Tanaka [41] improved the TRCA method by maximizing the similarity across group of subjects, and they named this novel method group TRCA. The results showed that the group representation calculated by the group TRCA method achieve high consistency between two domains and offer effective data supplementation during brain-computer interaction.…”
Section: Transfer Learning Based On Feature Representationmentioning
confidence: 99%
“…The results showed that this method significantly improves the information transfer rates and classification accuracy. Based on this research, Tanaka [41] improved the TRCA method by maximizing the similarity across group of subjects, and they named this novel method group TRCA. The results showed that the group representation calculated by the group TRCA method achieve high consistency between two domains and offer effective data supplementation during brain-computer interaction.…”
Section: Transfer Learning Based On Feature Representationmentioning
confidence: 99%
“…Critically, to get an optimal estimate of the tACS-targeted 8 Hz rhythm evoked by visual flicker, we applied spatio-spectral decomposition (SSD) to data from all seven parieto-occipital electrodes contralateral to the flicker [31]. SSD is a dimensionality reduction method that has been repeatedly applied in the framework of flicker-evoked response analysis to optimally extract rhythmic components in the data [32,33]. This procedure resulted in spatially weighted SSRSSD time series with larger signal-to-noise-ratio compared to single-channel analysis (Fig 3D).…”
Section: Individualization Of Physical Flicker Luminance Intensitymentioning
confidence: 99%
“…SSD maximizes signal power at the frequency of interest while simultaneously minimizing power at surrounding frequencies [31]. This procedure has been repeatedly applied in the framework of flicker-evoked response analysis [32,33]. Based on PLV topography, we computed SSD on all seven occipito-parietal electrodes contralateral to the flickering stimulus.…”
Section: Transcranial Electrical Stimulationmentioning
confidence: 99%
“…The xTRCA employs a temporal optimization to compensate for trial-by-trial latency variability, providing a better solution to enhance induced potentials than the conventional TRCA. Another extension is group TRCA (gTRCA) designed for group-level analysis [6]. The gTRCA finds linear coefficients that maximize not only trial-by-trial reproducibility within single subjects but also similarity across a group of subjects.…”
Section: Introductionmentioning
confidence: 99%